Optimizing Financial Performance: A Comprehensive Examination of Economic Value Added (EVA) and Market Value Added (MVA) at Telecommunication Companies in Indonesia - Adiandari, Ade Maharini; Anggara, I Komang Bayu (Yayasan Ilomata, 2024)
This research aims to determine the factors that influence the financial performance of telecommunications companies in Indonesia using the Economic Value Added (EVA) and Market Value Added (MVA) approaches. The background to this research arises from the need to understand how operational efficiency, financial policy, innovation, market competition, and economic conditions play a role in creating economic value and the market value of equity. Data collected from telecommunications companies during the 2017-2022 period formed the basis of the analysis, and the research methodology involved measuring EVA and MVA and assessing factors that influence financial performance. The results of this research provide in-depth insight into the complexity of the relationships between variables and their implications for the business strategy of telecommunications companies in Indonesia.